Hydraulic analysis of sediment stability due to waves in a Cavite offshore quarry zone - Bautista, Dominic M.
Materials that are used as fill for land reclamation projects in Manila bay are sourced from the Cavite Offshore Quarry Zone located 3 kilometers off the coast of Cavite. The sediment extraction from offshore dredging modified the seabed and showed large borrow pits in the area. The objective of this research is to determine the effects of these dredge pits on the wave climate and stability of sediments due to waves on the site. The study is composed of two major stages: the wave simulation stage and the sediment stability analysis stage. The model used in wave simulation is REF/DIF 1, a combined refraction-diffraction model that generates wave heights and wave angles on different points on the sites. These outputs are used to assess the wave climate on the area. Results suggest that waves converge in some regions outside the borrow pit area due to effects of depth variations. Also, decrease in wave heights is observed as waves propagate above the dredge pit due to the increase of water depth. For the sediment stability analysis stage, the maximum wave-induced bed shear stress is calculated using the drag law model where the wave friction factor is given by the formula of Swart (1974). The threshold shear stress, on the other hand, was calculated using the formula developed by She et al. (2006). Stability analysis was done by getting the ratio of the maximum bed shear stress and the critical shear stress. Unstable sediments have a ratio value of greater than 1. Results show that areas of sediment instability occur in shallow regions where the grain diameter is small and where bottom velocity is high. In conclusion, the effects of an offshore dredge pit in the coastal environment are not negligible and the methodology used in this research can be used as an assessment tool for future offshore dredging project plans.